ANALISIS MOBILE BANKING TERHADAP KINERJA KEUANGAN DENGAN MODERASI PROFITABILITAS ENTITAS PUBLIK PERBANKAN DI BEI - Aris Sunandes; Devaqi Lantu Rangga (Universitas Islam Balitar, 2022)
This study aims to analyze the effect of mobile banking on the financial performance of banking entities, profitability affects the financial performance of banking entities, profitability is able to moderate the influence of mobile banking on the financial performance of banking entities on the Indonesia Stock Exchange. The research method is explanatory research with banking data that has positive data values ​​with a total of 37 banking sectors. The results of the study that mobile banking has no effect on the financial performance of banking entities on the IDX. Profitability affects the financial performance of banking entities on the IDX, while profitability is unable to moderate the influence of digital banking on the financial performance of banking entities on the IDX.